Caracterização das propriedades ópticas e de spin de poços quânticos de InGaAsN/GaAs - Ballottin, Mariana Victória (2015)
In this work, it was investigated the optical and magneto-optical properties of In- GaAsN/GaAs and InGaAs/GaAs double quantum wells. It was performed a systematic experimental study of photoluminescence (PL) as a function of temperature, excitation power, polarization and applied magnetic field. It was investigated the effect of incorporation of N in these alloys, the thermal treatment effect, and the role of carrier localization effect on the optical and spin properties of these materials. The study of the PL as a function of temperature evidenced effects associated with the carriers' localization by defects incorporated by growth conditions at low temperatures. This effect was more pronounced for samples containing N. In optical emission measurements with applied magnetic field, it was found that the N samples presented lower diamagnetic shift, implying in larger carriers localization by defects, so corroborating the results for dependence of PL with temperature. Another important result was the reduction of the diamagnetic shift for samples without N after the thermal treatment, implying that, besides increasing the intensity of PL, the thermal treatment is creating defects responsible for the carriers' localization. The spin filter effect mediated by defects, with and without N, was investigated using photoluminescence technique with circularly polarized excitation. It was observed that the thermally treated samples showed a higher degree of circular polarization. This polarization increase was associated with the increased defect density after the thermal treatment and it is consistent with the results obtained for the diamagnetic shift. In general, the obtained results showed that such materials are interesting for possible applications like spin filters at room temperature.